2011
DOI: 10.1111/j.1525-139x.2011.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Neointimal Cells in Arteriovenous Fistulae: Bone Marrow, Artery, or the Vein Itself?

Abstract: The exact origin of the neointimal cells in arteriovenous fistulae (AVFs) has not been conclusively established. This study attempts to elucidate the anatomical source of neointimal cells in AVFs. Experimental fistulas were created in Lewis wild type (WT) and transgenic rats that constitutively expressed the Green Fluorescent Protein (GFP) in all tissues. AVFs were created by anastomosing the left renal vein to the abdominal aorta after unilateral nephrectomy. Three potential sources (bone marrow, feeding arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…In the absence of NO, other diffusible endothelium-derived factors, such as AngII and endothelin-1, lead to vasoconstriction, VSMC proliferation, and hypertrophic remodeling through their interaction with VSMC receptors (26). In agreement with this hypothesis, Skartsis et al (27) have shown that neointimal cells of experimental AVFs are derived from activated medial VSMCs.…”
Section: Ih Pathobiology Of Preexisting Ihsupporting
confidence: 61%
“…In the absence of NO, other diffusible endothelium-derived factors, such as AngII and endothelin-1, lead to vasoconstriction, VSMC proliferation, and hypertrophic remodeling through their interaction with VSMC receptors (26). In agreement with this hypothesis, Skartsis et al (27) have shown that neointimal cells of experimental AVFs are derived from activated medial VSMCs.…”
Section: Ih Pathobiology Of Preexisting Ihsupporting
confidence: 61%
“…The existence of stem cells in the fistula wall was recently suggested by Caplice et al (8), who described this type of cells as components of adventitial microvessels in the rat A-V fistula. A number of studies have proposed bone marrow-derived progenitor cells as the source of neointimal cells in stenotic blood vessels after arterial injury (38,44,46), but their contribution seems less pronounced in the case of venous hyperplasia, as clearly demonstrated in three independent studies (9,21,43). The present work highlights the critical role played by this pathway in A-V fistula remodeling.…”
Section: Discussionsupporting
confidence: 48%
“…The A-V fistula was created right after transduction. In parallel, four A-V fistulae were created with veins that had been transduced with a lentivirus (pLL-3.1) encoding green fluorescent protein (GFP) to assess transduction efficiency in the vascular wall using confocal microscopy (43).…”
Section: Methodsmentioning
confidence: 99%
“…Nearly half of the cells were green fluorescent protein positive in the neointima, suggesting that smooth muscle cells migrate from the carotid artery to the jugular vein in AVFs created in these mice (24). However, another recent study has shown contradictory results and suggests that neointimal cells are derived from local resident cells in the venous limb of the AVF (45). The issue of cells originating from the bone marrow has also been explored.…”
Section: Origins Of Neointimal Cells In Vascular Access Dysfunctionmentioning
confidence: 99%